Acquired fluconazole resistance and genetic clustering in Diutina (Candida) catenulata from clinical samples. (February 2023) - Nourrisson, Céline; Moniot, Maxime; Lavergne, Rose-Anne; Robert, Estelle; Bonnin, Virginie; Hagen, Ferry; Grenouillet, Frédéric; Cafarchia, Claudia; Butler, Geraldine; Cassaing, Sophie; Sabou, Marcela; Le Pape, Patrice; et al.
Abstract: Objectives: Diutina ( Candida ) catenulata is an ascomycetous yeast isolated from environmental sources and animals, occasionally infecting humans. The aim of this study is to shed light on the in vitro antifungal susceptibility and genetic diversity of this opportunistic yeast. Methods: Forty-five D . catenulata strains isolated from various sources (including human and environmental sources) and originating from nine countries were included. Species identification was performed using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and confirmed via internal transcribed spacer ribosomal DNA barcoding.  In vitro antifungal susceptibility was determined for seven systemic antifungals via the gradient strip method after 48 hours of incubation at 35°C using Etest® (Biomérieux) or Liofilchem® strips. Isolates exhibiting fluconazole minimal inhibitory concentrations (MICs) of ≥8 μg/mL were investigated for mutations in the ERG11 gene. A novel microsatellite genotyping scheme consisting of four markers was developed to assess genetic diversity. Results: MIC ranges for amphotericin B, caspofungin, micafungin, isavuconazole, and posaconazole were 0.19–1 μg/mL, 0.094–0.5 μg/mL, 0.012–0.064 μg/mL, 0.003–0.047 μg/mL, and 0.006–0.032 μg/mL, respectively. By comparison, a broad range of MICs was noted for fluconazole (0.75 to >256 μg/mL) and voriconazole (0.012–0.38 mg/L), the higher values being observed among clinical strains. The Y132F amino acid substitution, associated with azole resistance in various Candida species ( C . albicans, C . tropicalis, C . parapsilosis, and C . orthopsilosis ), was the main substitution identified. Although microsatellite typing showed extensive genetic diversity, most strains with high fluconazole MICs clustered together, suggesting human-to-human transmission or a common source of contamination. Discussion: The high rate of acquired fluconazole resistance among clinical isolates of D . catenulata is of concern. In this study, we highlight a link between the genetic diversity of D . catenulata and its antifungal resistance patterns, suggesting possible clonal transmission of resistant isolates.